Assessment of chemical, biochemical and ecotoxicological aspects in a mine soil amended with sludge of either urban or industrial origin - Alvarenga, P. (2013)
A greenhouse pot experiment was conducted to evaluate the effect of sewage sludge (SS), of sugar beet sludge (SBS), or of a combination of both, in the remediation of a highly acidic (pH 3.6) metal-contaminated soil, affected by mining activities. The SS was applied at 100 and 200 Mg ha 1 (dry weight basis), and the SBS at 7 Mg ha 1. All pots were sown with Italian ryegrass (Lolium multiflorum Lam.). After 60 d of growth, shoot biomass was quantified and analysed for Cu, Pb and Zn. The pseudo-total and bioavailable contents of Cu, Pb and Zn and the enzymatic activities of b-glucosidase, acid phosphatase, cellulase, protease and urease were determined in the soil mixtures. Two indirect acute bioassays with leachates from the soil (luminescent inhibition of Vibrio fischeri and Daphnia magna immobilization) were also used. The SS, in particular when in combination with SBS, corrected soil acidity, while increasing the total organic matter content and the cation exchange capacity. The application of SS led to a decrease in the level of effective bioavailable metals (extracted by 0.01 M CaCl2, pH 5.7, without buffer), but caused an increase in their potential bioavailability (extracted by a solution of 0.5 M NH4CH3COO, 0.5 M CH3COOH and 0.01 MEDTA, pH 4.7). Plant biomass increased more than 10 times in the presence of 100 Mg SS ha 1, and more than five times with the combined use of 100 Mg SS ha 1 and SBS, but a considerable phytotoxic effect was observed for the application rate of 200 Mg SS ha 1. Copper, Pb and Zn concentrations in the shoots of L. multiflorum decreased significantly when using 100 Mg SS ha 1 or SBS. The activities of b-glucosidase, urease and protease increased with increasing SS applications rates, but cellulase had a reduced activity when using 200 Mg ha 1 SS. Both amendments were able to suppress soil toxicity to levels that did not affect D. magna, but increased the soil leachate toxicity towards V. fischeri, especially with the application of 200 Mg SS ha 1. This study showed that for this type of mine soils, and when using SS of similar composition, the maximum SS application rate should be 100 Mg ha 1, and that liming the SS amended soil with SBS did not contribute to a further improvement in soil quality.